Isolation and characterization of a replication-competent molecular clone of an HIV-1 circulating recombinant form (CRF3301B) - Tee, K.K.; Kusagawa, S.; Li, X.J.; Onogi, N.; Isogai, M.; Hase, S.; Uenishi, R.; Liao, H.N.; Kamarulzaman, A.; Takebe, Y. (Public Library of Science, 2009)
A growing number of emerging HIV-1 recombinants classified as circulating recombinant forms (CRFs) have been identified in Southeast Asia in recent years, establishing a molecular diversity of increasing complexity in the region. Here, we constructed a replication-competent HIV-1 clone for CRF3301B (designated p05MYKL045.1), a newly identified recombinant comprised of CRF01AE and subtype B. p05MYKL045.1 was reconstituted by cloning of the near full-length HIV-1 sequence from a newly-diagnosed individual presumably infected heterosexually in Kuala Lumpur, Malaysia. The chimeric clone, which contains the 59 LTR (long terminal repeat) region of p93JP-NH1 (a previously isolated CRF01AE infectious clone), showed robust viral replication in the human peripheral blood mononuclear cells. This clone demonstrated robust viral propagation and profound syncytium formation in CD4(+), CXCR4-expressing human glioma NP-2 cells, indicating that p05MYKL045.1 is a CXCR4-using virus. Viral propagation, however, was not detected in various human T cell lines including MT-2, M8166, Sup-T1, H9, Jurkat, Molt-4 and PM1.p05MYKL045.1 appears to proliferate only in restricted host range, suggesting that unknown viral and/or cellular host factors may play a role in viral infectivity and replication in human T cell lines. Availability of a CRF3301B molecular clone will be useful in facilitating the development of vaccine candidates that match the HIV-1 strains circulating in Southeast Asia.